Shifting Gears: Changing Labor Relations in the U.S. Automobile Industry - Barkin, Solomon (Relations Industrielles / Industrial Relations, 1986)
This article reviews the book, "Shifting Gears: Changing Labor Relations in the U.S. Automobile Industry," by Harry C. Katz.